WS2 Quantum Dot Graphene Nanocomposite Film for UV Photodetection - Singh V.K.; Yadav S.M.; Mishra H.; Kumar R.; Tiwari R.S.; Pandey A.; Srivastava A. (My University, 2025)
The development of highly responsive, ultrathin, and cost-effective 0D-2D nanocomposite photodetectors, in which light absorption and carrier transportation may be realized separately and independently, has garnered considerable attention. In the present work, we demonstrate the fabrication of atomically thin UV photodetectors based on a hybrid structure (0D-2D) of semiconducting WS2 quantum dots (0D) with graphene (2D) on SiO2/Si substrate. Graphene and WS2 quantum dots (WS2-QDs) are synthesized through chemical vapor deposition (CVD) and hydrothermal processes, respectively. The proposed photodetector offers a remarkable response to ultraviolet (UV) light of ∼365 nm, owing to the high absorption efficiency of WS2-QDs and excellent charge mobility of graphene. The photodetector exhibits high responsivity of ∼1814 A W-1 under illumination of UV light (365 nm, power density of 50.74 μW cm-2) and a high photodetectivity of ∼7.47 × 1012 Jones (cm Hz1/2 W-1). The photodetector fabricated in this work shows a fast photoresponse time of ∼2 s (rise time) and ∼2.9 s (fall time). We have also elucidated the working principle of the proposed photodetector. Outcomes of the present work are comparable or better than other results available in the literature. Our findings suggest that this nanocomposite structure of WS2-QDs with graphene sheets is a prospective candidate for high-performance optoelectronic devices. © 2019 American Chemical Society.